Efek Aditif Ekstrak Betasianin dari Kulit Buah Naga (Hylocereus polyrhizus) Terhadap Kadar Asam Laktat Sinbiotik Set Yoghurt - Munita, Azizah; Putri, Selvi Apriliana; Azhar, Minda (Departemen Kimia FMIPA UNP, 2024)
The use of synthetic food coloring raised the risk of chronic diseases, which was a serious problem in the food industry. To overcome this, a study was carried out on functional foods, especially synbiotic yogurt set, to evaluate betacyanin as a natural dye that had antioxidant properties. The goal was to provide an alternative solution to counteract free radicals, which are known to contribute to chronic diseases. This study examined the effect of betacyanin extract on lactic acid levels using homolactic fermentation. The experiment method involved a triplicate pattern, and different variations of betacyanin extract (5 mL, 10 mL, and 15 mL) were tested, alongside a negative control consisting of the synbiotic yogurt set without the addition of betacyanin extract. Statistical analysis, including One Way ANOVA and Tukey's test with GraphPad Prism 10.0, demonstrated that betacyanin had a significant impact on lactic acid levels. The synbiotic yogurt set with 15 mL of betacyanin extract exhibited the highest lactic acid content (1.88%), while the negative control displayed the lowest lactic acid content (0.98%). These findings indicate that betacyanin, as a natural dye, that had antioxidant properties and was capable of increasing the lactic acid content in the synbiotic yogurt set.Keywords — Betacyanine, red dragon peel, synbiotic set yogurt, lactic acid.